2003
DOI: 10.1002/prot.10504
|View full text |Cite
|
Sign up to set email alerts
|

Docking studies and model development of tea polyphenol proteasome inhibitors: Applications to rational drug design

Abstract: Previously, we demonstrated that natural and synthetic ester bond-containing green tea polyphenols were potent and specific non-peptide proteasome inhibitors. However, the molecular mechanism of inhibition is currently unknown. Here, we report that inhibition of the chymotrypsin activity of the 20S proteasome by (-)-epigallocatechin-3-gallate (EGCG) is time-dependent and irreversible, implicating acylation of the beta5-subunit's catalytic N-terminal threonine (Thr 1). This knowledge is used, along with in sili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
130
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 36 publications
(62 reference statements)
13
130
0
1
Order By: Relevance
“…The docking analyses, in conjunction with the Lineweaver-Burk analysis and the fluorometry data showing FRET between EGCG and PME indicate direct interaction of EGCG at the catalytic binding site of PME and competitive inhibition. Such interactions may be mediated via hydrophobic interactions at the S1 pocket residing at the catalytic site as suggested by Smith et al (2004).…”
Section: Fluorometry Of Pme Interaction With Egcg Shows Reduced Enzymmentioning
confidence: 99%
“…The docking analyses, in conjunction with the Lineweaver-Burk analysis and the fluorometry data showing FRET between EGCG and PME indicate direct interaction of EGCG at the catalytic binding site of PME and competitive inhibition. Such interactions may be mediated via hydrophobic interactions at the S1 pocket residing at the catalytic site as suggested by Smith et al (2004).…”
Section: Fluorometry Of Pme Interaction With Egcg Shows Reduced Enzymmentioning
confidence: 99%
“…Polyphenolic antioxidants such as EGCG have been shown to possess cancer chemopreventative activity, mediated by several mechanisms that are postulated to stem either from its antioxidant effects as a ROS (reactive oxygen species) scavenger [6] or by direct inhibition of molecular targets [47][48][49]. The antioxidant activity of EGCG has been shown to regulate multiple signal transduction pathways [43,50] including the activities of several oxidative stress-responsive transcription factors such as NF-κB, AP-1 and Nrf2.…”
Section: The Human Brf2 Promoter Activity Is Inhibited By Egcgmentioning
confidence: 99%
“…Analysis revealed that structure 5 and 7 possessed two sites with similar susceptibility whereas structure 16 and 21 possessed a single site (Fig. 2), suggesting that these sites could be attacked, and subsequently covalently bound, by the OH group of N-Thr of proteaosmal ß5 subunit (22). For better understanding of the possible chemical nature of these four analogs to inhibit the chymotrypsin-like activity of the proteasome, each was docked to the active site of the proteasome ß5-subunit, which is responsible for the chymotrypsin-like activity (22).…”
Section: Resultsmentioning
confidence: 99%
“…In silico docking was performed on a Linux Red Hat 9.0 based platform using AutoDock 3.0. The AutoDock suite of programs, which was used for the docking calculation, employs an automated docking approach, allowing ligand flexibility as described to a full extent elsewhere (22). AutoDock has been compared with various other docking programs and has been found to be able to locate docking modes that are consistent with X-ray crystal structure (23)(24)(25)(26).…”
Section: Molecule Building and Nucleophilic Susceptibility Analysismentioning
confidence: 99%